Two Decades Since Cms V. Argentina: Concession Contracts, Necessity Doctrine, And the Imf’s Impact on Sovereign Economic Governance - Saied Abdallah, Esraa S. (AUC Knowledge Fountain, 2026)
In the evolving landscape of international trade, particularly within the framework of Bilateral Investment Treaties (BITs), the primary aim has been to promote and protect foreign investment. The 1980s witnessed a notable increase in investment treaties, coinciding with a global shift toward privatization that was significantly influenced by the impact of international financial institutions, including the International Monetary Fund (IMF) and the World Bank. By the 1990s, BITs had evolved to offer specific guarantees aimed at reducing the risks foreign investors faced in host states. However, despite the growth and transformation brought about by foreign investments, disputes arising under investment treaties can pose significant challenges to both the investment infrastructure within host states and the principle of state sovereignty. This thesis revisits Argentina’s response to the 1999–2001 economic crisis, emphasizing the invocation of the necessity doctrine under customary international law and the U.S.-Argentina Bilateral Investment Treaty (BIT). The case illustrates how external financial pressures, particularly those imposed by the International Monetary Fund (IMF), constrained Argentina's ability to safeguard its national interests while adhering to international legal obligations. Furthermore, this study highlights the interpretative challenges surrounding the necessity doctrine and its potential misapplication in justifying state actions during economic turmoil. The findings reveal that while Argentina sought to protect its economy through emergency measures, these actions were often scrutinized within the framework of international investment law, raising questions about accountability and state sovereignty.